Impact of endobiliary radiofrequency ablation on survival of patients with unresectable cholangiocarcinoma: a narrative review - Di Girolamo, Elena; Belli, Andrea; Ottaiano, Alessandro; Granata, Vincenza; Borzillo, Valentina; Tarotto, Luca; Tatangelo, Fabiana; Palaia, Raffaele; Civiletti, Corrado; Piccirillo, Mauro; D’Angelo, Valentina; Fiore, Francesco; et al. (Frontiers in Oncology, 2023)
Cholangiocarcinoma (CCA) is a rare cancer originating from the biliary epithelium and accounts for about 3% of all gastrointestinal malignancies. Unfortunately, the majority of patients are not eligible for surgical resection at the time of diagnosis, because of the locally advanced stage or metastatic disease. The overall survival time of unresectable CCA is generally less than 1 year, despite current chemotherapy regimens. Biliary drainage is often required as a palliative treatment for patients with unresectable CCA. Recurrent jaundice and cholangitis tend to occur because of reobstruction of the biliary stents. This not only jeopardizes the efficacy of chemotherapy, but also causes significant morbidity and mortality. Active control of tumor growth is crucial for prolonging stent patency and consequently patient survival. Recently, endobiliary radiofrequency ablation (ERFA) has been experimented as a treatment modality to reduce tumor mass, and delay tumor growth, extending stent patency. Ablation is accomplished by means of high-frequency alternating current which is released from the active electrode of an endobiliary probe placed in a biliary stricture. It has been shown that tumor necrosis releases intracellular particles which are highly immunogenic and activate antigen-presenting cells, enhancing local immunity directed against the tumor. This immunogenic response could potentially enhance tumor suppression and be responsible for improved survival of patients with unresectable CCA who undergo ERFA. Several studies have demonstrated that ERFA is associated with an increased median survival of approximately 6 months in patients with unresectable CCA. Furthermore, recent data support the hypothesis that ERFA could ameliorate the efficacy of chemotherapy administered to patients with unresectable CCA, without increasing the risk of complications. This narrative review discusses the results of the studies published in recent years and focuses on the impact that ERFA could have on overall survival of patients with unresectable cholangiocarcinoma. This work was supported by the Italian Ministry of Health – “Ricerca Corrente Funds L4/2”